A genre analysis of review articles in applied linguistics / Ali Sorayyaei Azar - Ali Sorayyaei , Azar (2017)
The aim of the present research was to draw on Swales’ move analysis in order to analyze review articles in applied linguistics. This research was conducted using a mixed methods research approach (qualitative and quantitative methods). It adopted both genre analysis and corpus-based study to reach a comprehensible understanding of the review article genre in applied linguistics. More specifically, the objectives were: (1) to describe and analyze the review article genre in applied linguistics and propose a classification system for it, (2) to analyze and identify rhetorical move structures commonly used in the prevalent sections of review articles, (3) to identify and describe the argumentative patterns commonly employed in the thematic units of the Body section, and (4) to investigate attitude markers and self-mention resources used in review articles to indicate writers’ stance, evaluation and authorial identity. To this end, the data were drawn from a randomly selected corpus of thirty-two review articles, published between 2000- 2007, from a discipline-related key journal in applied linguistics. Using both qualitative and quantitative approaches, the corpus was firstly described and classified into the three types of review articles namely (a) critical evaluative review article, (b) bibliographic review article, and (c) mixed-mode review article. Subsequently, the rhetorical move structures of the Abstract, Introduction and Conclusion sections were analyzed and discussed. The linguistic features were also highlighted for the moves in the three analytical sections. The findings indicated that there were four major moves in the Abstract section, three major moves in the Introduction section and three major moves in the Conclusion section. The rhetorical move structures of all three types of review articles were also compared to find out the similarities and differences between the three types of review articles. It was found that there were generic variations within these three types of review articles in terms of moves and strategies used in the analytical sections. The results also revealed which argumentative pattern was employed in the theme-bound units. The scope for genre analysis of the thematic units was narrowed down to the analytical framework used by Hatim and Mason (1990) for argumentative discourses. The findings highlighted that the writers in the thematic units argued ideas, presented evaluation and left an authorial footprint of argumentation through different textual strategies. These strategies varied from counter argumentative to through argumentative strategies. The analysis of the thematic units indicated that argumentative discourses followed specific text type patterns which were highly recursive and complex. Finally, the two stance features, particularly attitude markers and self-mention resources of Hyland’s (2005b) interaction taxonomy, were analyzed in review articles. These two features were investigated by Wordsmith tools version 6 (Scott, 2011). The overall frequency of the use of attitude markers and self-mentions and their relevant categories in the entire corpus were analyzed. The findings indicated that there were considerable variations in the use of two stance features across the different analytical sections and the two sub-corpora (i.e. the critical evaluative and bibliographic review articles). It is hoped that the results of this research will be of use to junior researchers and EFL postgraduates who seek to review the developments critically during their research writing.